Biological Activities of Castela coccinea Griseb: Extracts - Campagna, Maria Noel (2011)
Infusions of leaf and bark of Castela coccinea Griseb. (Simaroubaceae) were traditionally used against dysentery. In this work, anti-bacterial and antioxidant activity were studied in C. coccinea extracts. The higest DPPH scavenging activity was detected in ethanolic leaf extracts with an IC50= 0.015 mg/ml. Bark ethanolic extracts showed inhibition of lipoperoxidation and free radical scavenging. However, a previous work evidenced that this extract is toxic at a concentration needed to show antioxidant activity. It might be consider that wood could be used instead of bark extract as the first one showing higher scavenging activity (Wood 55 %, Bark 33 % of DPPH scavenging) and good inhibition of lipoperoxidation. It is a very interesting fact the high tannin and mucilage content, which are localized particularly in leaves. The high antioxidant activity and abundant mucilage and tannin contents could justify, at least in part, its popular use.